Efficacy of a Novel Bi-Steric mTORC1 Inhibitor in Models of B-Cell Acute Lymphoblastic Leukemia - Lee, Bianca J.; Mallya, Sharmila; Dinglasan, Nuntana; Fung, Amos; Nguyen, Tram; Herzog, Lee-or; Thao, Joshua; Lorenzana, Edward G.; Wildes, David; Singh, Mallika; Smith, Jacqueline A. M.; Fruman, David A. (Frontiers in Oncology, 2021)
The mechanistic target of rapamycin (mTOR) is a kinase whose activity is elevated in hematological malignancies. mTOR-complex-1 (mTORC1) phosphorylates numerous substrates to promote cell proliferation and survival. Eukaryotic initiation factor 4E (eIF4E)-binding proteins (4E-BPs) are mTORC1 substrates with an integral role in oncogenic protein translation. Current pharmacological approaches to inhibit mTORC1 activity and 4E-BP phosphorylation have drawbacks. Recently we described a series of bi-steric compounds that are potent and selective inhibitors of mTORC1, inhibiting 4E-BP phosphorylation at lower concentrations than mTOR kinase inhibitors (TOR-KIs). Here we report the activity of the mTORC1-selective bi-steric inhibitor, RMC-4627, in BCR-ABL-driven models of B-cell acute lymphoblastic leukemia (B-ALL). RMC-4627 exhibited potent and selective inhibition of 4E-BP1 phosphorylation in B-ALL cell lines without inhibiting mTOR-complex-2 (mTORC2) activity. RMC-4627 suppressed cell cycle progression, reduced survival, and enhanced dasatinib cytotoxicity. Compared to a TOR-KI compound, RMC-4627 was more potent, and its effects on cell viability were sustained after washout in vitro. Notably, a once-weekly, well tolerated dose reduced leukemic burden in a B-ALL xenograft model and enhanced the activity of dasatinib. These preclinical studies suggest that intermittent dosing of a bi-steric mTORC1-selective inhibitor has therapeutic potential as a component of leukemia regimens, and further study is warranted.